Hybrid SAFE-GMM approach for predictive modeling of guided wave propagation in layered media. (15th August 2019) - Joseph, Roshan; Li, Lingfang; Haider, Mohammad Faisal; Giurgiutiu, Victor
Highlights: Steel/CFRP strips bonded to the surface of concrete beams strengthen the structure. Guided wave SHM of such layered media can be done by the SAFE method. SAFE has an efficient root-solving capability. SAFE method has discontinuity of stress prediction at the interface of layered media. Hybrid SAFE-GMM can obtain guided wave stress modeshape accurately in layered media. Abstract: Dispersion curve, and displacement modeshapes of multilayer structures can be obtained using Semi-Analytical Finite Element (SAFE) method. Stress mode shapes calculated from SAFE were discontinuous at the interface, because SAFE method formulation does not apply stress continuity at the interface. A case study of 1 mm aluminum-1 mm steel double-layer plate is presented, showing the SAFE stress predictions at the interface. The results observed were discontinuity of out-of-plane stress modeshapes at the interface. Mesh refinement was performed at the interface to study the convergence of stress mode shapes at the interface, yet the stress discontinuity problem was not solved. A fine mesh at the interface was created by using variable mesh techniques. This also did not provide continuous stress mode shape at the interface. Therefore, in this paper, a novel hybrid SAFE-GMM (Global Matrix Method) approach was used to obtain stress mode shapes accurately and efficiently. GMM develops the displacement and stress equations for individual layers in a multilayered structure and assembles a global matrix by applying the boundary and interface continuity conditions. A case of practical importance, CFRP strengthened concrete structure was analyzed using the SAFE-GMM approach. The drawback of the SAFE technique to this case is also presented, and it shows that the hybrid SAFE-GMM approach gave the interface stresses accurately.